Development of Integrated Student Worksheets (LKPD) of Al-Quran Verses on the Subtheme of How the Body Processes Clean Air for Grade V MI Students: Development Study with 4D Model - Bintang, Bintang; Muhaemin, Muhaemin; Mirnawati, Mirnawati; Fauzia, Rizkinur; Atmasudirja, Ivan Priyana; Da Costa, Mohammad Anwar (Journal of Indonesian Islamic Studies, 2024)
This study aims to develop Student Worksheets (LKPD) on the subtheme "How the Body Processes Clean Air" integrated with verses of the Qur'an for fifth grade students at MI Al-Manar Lamone, using the 4D development model (Define, Design, Develop, Disseminate). The development process begins with the needs analysis stage involving analysis of students, materials, and teachers, followed by designing LKPD according to the thematic framework. At the development stage, LKPD was tested for validity by three experts, namely religious experts, material experts, and language experts. The validation results showed that this LKPD met the valid criteria with an average percentage of 89.3%. Furthermore, the practicality test also produced a percentage of 82%, which is included in the very practical category. The results of the practicality and product effectiveness tests show that this LKPD can be used effectively in increasing students' interest and motivation to learn, as well as enriching their understanding of learning materials with an integrative approach based on religion. Thus, this LKPD is suitable for use in learning and has the potential to make a significant contribution to improving the quality of education.